Hate is too great a burden to bear: Hate crimes and the mental health of refugees - Daniel Graeber; Felicitas Schikora (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Against a background of increasing violence against non-natives, we estimate the effect of hate crime on refugees' mental health in Germany. For this purpose, we combine two datasets: administrative records on xenophobic crime against refugee shelters by the Federal Criminal Office and the IAB-BAMF-SOEP Survey of Refugees. We apply a regression discontinuity design in time to estimate the effect of interest. Our results indicate that hate crime has a substantial negative effect on several mental health indicators, including the Mental Component Summary score and the Patient Health Questionnaire-4 score. The effects are stronger for refugees with closer geographic proximity to the focal hate crime and refugees with low country-specific human capital. While the estimated effect is only transitory, we argue that negative mental health shocks during the critical period after arrival have important long-term consequences.
Keywords: I10; J15; J24; F22; O15; 330; Mental health; hate crime; migration; refugees; human capital